Management of Adult Groin Hernia in Denmark: a National Updated Consensus - M. Kirk; N. A. Henriksen; M. W. Christoffersen; K. Andresen; A. Dorfelt; M. Krogsgaard; L. Pejtersen; T. Sommer; N. Wensel; N. B. Zinther; F. Helgstrand; J. Rosenberg (Journal of Abdominal Wall Surgery)
This article presents the updated Danish national recommendations for the treatment of groin hernias, developed by the Danish Hernia Database steering committee and based on consensus. In alignment with the 2023 European Hernia Society guidelines, a minimally invasive approach is now the preferred strategy for most patients with primary inguinal and femoral hernias, regardless of age or gender. The recommendations emphasize individualized decision-making based on clinical presentation, hernia type, and patient preferences while also integrating national surgical traditions and practices. Key topics include diagnostic criteria, indications for surgery, surgical techniques, management of recurrence, perioperative considerations, and postoperative convalescence. Special attention is given to nerve handling, management of the round ligament in women, and recommendations for both elective and emergency cases. Additionally, the guidelines address changes in surgical education necessitated by the shift toward minimally invasive procedures. The present recommendations apply to Denmark only. These recommendations are adapted to the Danish healthcare environment and may not be directly transferable to other countries, as they reflect local surgical routines, resource availability, and population-specific considerations.